The effects of self-efficacy development program on knowledge and attitude about electronic cigarettes of nursing student leaders - Takaree, Sukrita; Janthanakul, Pichaporn; Panjinda, Wattanee; Samsee, Siriporn (Thai Journal of Nursing, 2024)
This quasi-experimental research aims to study the effects of self-efficacy development program on knowledge and attitude about electronic cigarettes of nursing student leaders. Using a method of purposive sampling, a total of sixty third-year nursing students was selected as participants. They were randomly divided into the experimental and the control groups, with 30 in each. Data collection tools included the personal information questionnaire and the questionnaire on knowledge and attitude about electronic cigarettes, and self-efficacy. This questionnaire comprises knowledge about the dangers of e-cigarettes, attitudes towards e-cigarettes, and self-efficacy. Data were analyzed using descriptive statistics and t-test. The results showed that after the experiment, knowledge and self-efficacy in the experimental group were significantly higher than those in the control group but attitude towards electronic cigarettes was significantly lesser than those in the control group at p < .05.